Strategi Jaringan Advokasi Transnasional Greenpeace Indonesia Terkait Isu Deforestasi Hutan Indonesia oleh Wilmar International - Virgy, Muhammad Arief; Djuyandi, Yusa; Darmawan, Wawan Budi (Journal of Political Issues, 2020)
Greenpeace Indonesia looking for Wilmar International as actor for making deforestation.. Greenpeace Indonesia pressured Wilmar International to commit to implementing their No Deforestation, No Peat, No Exploitation (NDPE) policy through the establishment of a transnational advocacy network to make enough power to put pressure on Wilmar International. Through this method, Greenpeace Indonesia succeeded in making Wilmar International pressured and changed its behavior. This research analyzes how Greenpeace Indonesia's strategy in forming transnational advocacy networks so that the network suppresses and monitors the behavior of target actor through the Keck & Sikkink Transnational Advocacy Network theory. Researchers used qualitative methods with a case study approach. Data collection comes from primary and secondary data and data collection through literature studies from books, journals and articles. The results of this study indicate that Greenpeace Indonesia is very optimal in carrying out Information Politics and Leverage Politics strategies. Greenpeace Indonesia has creative and confrontational methods in implementing the Symbolic Politics strategy. But the weakness of this strategy is that Greenpeace Indonesia seems to be exclusive in carrying out its actions by other environmental NGOs, especially domestic-based environmental NGOs. The weaknesses of these four strategies are Accountability Politics where Greenpeace Indonesia does not have the commitment of Wilmar International which has binding legal force.